Climate-change adaptation among Smallholder farmers in zambia - Ndhlovu, Obrian (School of Economics, 2024)
In Zambia, climate variability has resulted in declining and more erratic rainfall. Soil fertility has also declined, mainly from over use and use of environmentally unfriendly farming methods. These factors have contributed to declining farm productivity and revenue, leading to increased poverty levels in rural areas and undermining efforts to achieve sustainable development goals on poverty eradication and ending hunger. The country has been promoting adaptation practices such as conservation farming, crop diversification and irrigation in order to help smallholder farmers adapt to the climate. Despite these efforts, observation suggests suboptimal levels of adaptation. In three substantive chapters, this thesis investigates the strategies smallholder farmers use to adapt to variability in rainfall, the impact of policy reforms on adoption of sustainable farming practices, and whether farmers find these practices beneficial. The thesis has the potential to inform policy on climate adaptation, the effectiveness of input support programme reforms on influencing farmer behaviour and the relevance of new climate smart agricultural technologies in the climate adaptation agenda. The thesis also proposes measures of household variables, such as education and gender, that capture information beyond the head of household as is common in the literature. Chapter 2 assesses farmers' responses to variability in rainfall and investigates drivers behind adaptation strategy choice, including the adoption of conservation farming and other climate adaptation strategies such as crop diversification and irrigation. The seemingly unrelated regression estimation is used to investigate the adoption of farming practices while the ordered Probit and Tobit models are used to analyse the magnitude and intensity of adoption, respectively. The chapter contributes to the literature on climate adaptation by analysing adoption in a more broader sense by looking at the diversity and intensity of adoption, employing methods that are robust to interrelationships among adaptation strategies, the use of unique data combining quantitative and qualitative data, which enables the chapter to provide context to the findings. The results show that the level of adoption of conservation farming, crop diversification and irrigation remains low. There is also evidence of adoption reversal. The major challenges to adoption include low level of access to complementing practices such as use of herbicides, the practice of open grazing, the entrenched culture of maize monocropping, which is exacerbated by general lack of structured input and output markets for alternative crops. This calls for the scaling up of agricultural extension services to support skills and knowledge acquisition for the adoption of new farming practices, including the use of herbicides. Chapter 3 evaluates the impact of input subsidy programme reforms on the adoption of crop diversification and rotation practices among smallholder farmers. The difference-in-differences approach in combination with propensity weighting/matching and endogenous treatment approach is employed. The findings have the potential to inform the ongoing reforms in the agricultural subsidy programme. While the analysis of agricultural input subsidy programme pursue primary objectives such as the impact on fertiliser use, crop yield and hunger or poverty, this chapter analyses the impact of such programmes in facilitating climate adaptation, which may be considered a secondary objective and not well understood. The chapter also employs a unique data structure that permits the identification of treatment effect. The results show that the opening up of the input subsidy to multiple crops had a significant positive impact on household crop diversification. The electronic voucher system, although having a positive impact on crop diversification and crop rotation, has been hampered by the general inertia in the private markets to provide certified inputs of other crops. In addition, the lack of assured markets for outputs of other crops compared to maize has worked against efforts to stimulate crop diversification and rotation. These results suggest that reforms to the subsidy programme must be complemented by parallel reforms in other aspects of agriculture, such as extension services and agricultural markets, if they are to be effective in catalysing or facilitating adaptation to rainfall variability. Chapter 4 uses plot level data to evaluate the effect of conservation farming on crop yields and downside risk measured using the skewness based measure. The chapter uses the multinomial endogenous treatment effects models to analyse the impact on crop yield and climate-resilience, respectively. The chapter contributes to literature by employing methods that account for the endogenous household level decision to assign CF practices on different crop plots and has the potential to inform the ongoing drive to promote climate adaptation among smallholder farmers. Plot level evidence shows that crops to which some components of conservation farming are applied tend to have higher yields when rainfall is low. Results also show that crops of farmers who adopt and implement some components of conservation farming are also more likely to survive. These results call for the promotion of the full adoption of conservation farming and other complementing technologies, especially in low rainfall agro-ecological zones, where its impact will be most appreciated